Fertilizer Recommendation for Chilli-Garlic Intercropping System (Bangladesh Agronomy Journal, 2022)
An experiment was conducted at Central Research Farm, BARI, Gazipur and On Farm Research Division, BARI, Noakhali during Rabi season of 2017-18, 2018-19 and 2019-20 to develop a fertilizer recommendation for chilli with garlic intercropping system. Six treatment combinations viz. T1= 100% RDCF of chilli + 0% RDCF of garlic, T2= 100% RDCF of chilli +10% RDCF of garlic, T3= 100% RDCF of chilli + 20% RDCF of garlic, T4= 100% RDCF of chilli +30% RDCF of garlic, T5= 100% RDCF of chilli +40% RDCF of garlic and T6= 100% RDCF of chilli +50% RDCF of garlic were tested. The experiment was laid out in randomized complete block design with 3 replications. Both chilli and garlic characters significantly influenced by different treatment combinations. The maximum yield of chilli (10.12 and 9.10 t ha-1 at Gazipur and Noakhali, respectively) and garlic (3.70 and 3.55 t ha-1 at Gazipur and Noakhali, respectively) were obtained from T6 treatments which were statistically similar with T5 treatment. Chilli equivalent yield progressively increased with the increase of inorganic fertilizers. The results showed that T6 provided the highest CEY (17.52 and 16.18 t ha-1 at Gazipur and Noakhali, respectively) followed by T5 (17.47 and 16.14 t ha-1 at Gazipur and Noakhali, respectively). The highest gross margin (Tk. 339755 ha-1 and Tk 310198. ha-1at Gazipur and Noakhali, respectively) as well as BCR (4.50 and 4.32 at Gazipur and Noakhali, respectively) were obtained from T5 treatment while the lowest net return (Tk. 266661 ha- 1 and Tk. 242264 ha-1at Gazipur and Noakhali, respectively) as well as BCR (3.92 and 3.76 at Gazipur and Noakhali, respectively) were observed from T1 treatment. Though T6 treatment gave higher yield over all the treatments but it showed lower BCR compared to T5 treatment due to higher cost involvement for inorganic fertilizer.Bangladesh Agron. J. 2022, 25(1): 7-14